Pengaruh Motivasi dan Kesejahteraan Karyawan Terhadap Kinerja Karyawan di PT Lemo Express Transindo - Daeli, Susina; Marwansyah, Sofyan (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to determine the influence of motivation and well-being on performance. The research hypothesis tested is that there is a significant influence between motivation and well-being on performance at PT. Lemo Express Transindo. The research methods used were observation, questionnaires, and documentation studies. The observation technique involved direct observation of employees at work. The questionnaire technique involved distributing questionnaires to 31 employees to collect data by asking each employee to answer the statements listed in the questionnaire. The documentation study technique involved taking photographs during the observation. To determine the extent of the influence of motivation and employee well-being on performance, the authors used quantitative techniques, including validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and coefficient of determination tests, all processed using SPSS 2025. The results showed that partially, work motivation and employee well-being had no significant effect on employee performance. However, simultaneously, work motivation and employee well-being significantly influenced employee performance, contributing 30%, while the remainder was influenced by other factors outside the study